(3UhQI GdeQCI aj GdEYdGe GdYQHj (B/s - (3NVhQ, COjHs ((3GdLRGFQ (B:s (3OGQ GdCjGe ,s, 1999)
(3jJejR ehVhY GdeQCI HbOQ cHjQ ef GdMSGSjI h Pdc dCfg GdehVhY GdPj jYcS h jLSO efXheI GdGacGQ h Gdbje ddQO h ddLeGYI (B.(3dGJYed hSGFd GdZYdGe GdYQHjI aj aQGZ ceG GfgG de JGJ ef GdYOe h dG JJhLg Edi GdeWdb ZfgG GOhGJ efgecI aj JMbjb GSJQGJjLjGJ h SjGSG ef ChLOgG (B. (3aj VhA Pdc jXgQ eOi JYbjO SDGd (B: (3eGgj CHQR edGeM GdUhQI GdJj JQSegG h JbOegG hSGFd GdEdGe GdYQHjI ddeQCI h gd gfGc UhQI hGMOI GhUhQG eJYOOI (B. (3Ke eGgj YfGUQ gPg GdUhQI (B. (3h eGgj OhGaY chjfgG h eGgj GdeUGdM GdJj JNOegG h GdEjOjhdhLjI GdJj JeKdgG? h gd JfSLe gPg GdUhQI eY GdUhQI GdhGbYjI ddeQGI GdYQHjI ? h gd JeKd GSJeQGQG Ge GfbWGYG aj GdfXQI Gdi GdeQCI ? h cja GfYcSJ gPg GdUhQI Ydi GdEYdGe GdfSGFj GdYQHj (B. (3jMGhd gPG GdHMK efGbTI gPg GdCSFdI h GdELGHI YfgG HgOa GdJYQa Ydi GdeeGQSI GdEYdGejI GdYQHjI h JbhjegG h GdhUhd Gdi CSJfJGLGJ JSGge aj hVY GdeeGQSI GdEYdGejI Ydi CSGS Ydej h HGdJGdj JSGgeaj QaY eSJhGgG h GfVGLgG(B. s
Keywords: (3GdEYdGe GdYQHjs; (3GdeQCI s; (3GdeQCI GdYQHjIs